Community Vulnerability to Lake Drought in Muara Enggelam Village - Anwar, Yaskinul; Muhammad, Irmawati; Nurlita, Aulia; Mislan, Mislan (Poltanesa, 2024)
Drought vulnerability epitomizes a community's capacity to cope with drought-related calamities. In Muara Enggelam Village, the susceptibility to lake drought stems from diminished rainfall and lake water levels plummeting below 4.5 meters, as documented by the Mahakam River observation station in Kota Bangun. Consequently, the study focuses on the manifestation of lake drought vulnerability within Muara Enggelam Village. The research methodology encompasses a multifaceted approach involving observation, documentation, interviews, and questionnaires to gauge vulnerability levels. These assessments were based on key indicators of exposure, sensitivity, and adaptive capacity. Employing a cluster random sampling technique, 75 respondents were selected to represent the village population. Data analysis entailed the application of scoring and weighting methodologies. The outcomes of the study reveal that Muara Enggelam Village falls within Zone D, denoting high sensitivity as the primary component of vulnerability. Specifically, the indicators yield values of 0.41 for exposure intensity (EI), 0.81 for sensitivity intensity (SI), and 0.49 for adaptive capacity intensity (CI). The highest sensitivity observed in the village can be attributed to factors such as low-income levels and a significant proportion of the population engaged in fishing activities. In conclusion, this research sheds light on the intricate dynamics of drought vulnerability in Muara Enggelam Village, emphasizing the urgent need for targeted interventions to bolster the community's resilience against future drought events.